Achilles tendon rupture in an elite athlete following multiple injection therapies - Hamilton, B.; Remedios, D.; Loosemore, M.; Maffulli, N. (Journal of Science and Medicine in Sport, 2008)
Achilles tendinopathy is common, and its management continues to be challenging, especially in elite athletes. Despite a wide range of novel management options, none guarantees a rapid return to high level sporting activity. Eccentric exercise has been shown to reduce symptoms and normalise imaging abnormalities, but time constraints on professional athletes often make this an unrewarding isolated management strategy. Eccentric exercises concurrent with ongoing training may not be as successful as eccentric training alone, reducing one's confidence in this modality for the "in-season" tendinopathy in the elite athlete. When a professional athlete is faced with a tendinopathy recalcitrant to eccentric exercise, manual therapy and orthotics, a more invasive approach is often attempted to expedite a return to unencumbered training. Numerous injection therapies are described, ranging from homeopathic products to glucocorticosteroids. The robustness of the literature surrounding these techniques is variable, but when an athlete is desperate to return to full training, clinicians working with elite athletes are often tempted to utilise more empirical management options. We present a patient who illustrates the potential dangers of injection therapy in the elite athlete, in particular sequential injection therapy involving vascular sclerosants, which to our knowledge has not previously been described. Written consent for the presentation of this case was obtained from the athlete concerned.